Reforma el artículo 107 literal C segundo inciso de la ley de seguridad social y su contraposición con la constitución de la República del Ecuador. - Altamirano Luicin, Luis Alberto (2015)
"The right of Social Security is an inalienable right of all the people , and will be paramount duty and responsibility of the State " , the model of our Constitution is to protect the fundamental rights of citizens. In our social system the State not only protects the rights of individuals, but also for compliance with the basic principles outlined in the Constitution such as solidarity , obligation , universality , equity, efficiency , subsidiarity , adequacy, transparency and participation.